Given a positive integer n , let M ( n ) be the largest integer m such that
( n − 1 m ) > ( n m − 1 ) .
Then n → ∞ lim n M ( n ) = c a + b , where a , b , and c are coprime integers. Find a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We need
( n − 1 ) ! ⋅ ( m − n + 1 ) ! m ! > n ! ⋅ ( m − n − 1 ) ! ( m − 1 ) !
After simplifying, we need to solve for m in the quadratic inequality
m 2 − ( 3 n − 1 ) m + ( n 2 − n ) < 0
For, the largest value of m for a given n, we simply need the bigger root of the inequality given.....i.e.
M ( n ) = 2 3 n − 1 + 5 n 2 − 2 n + 1
Now, simply taking the limit of the desired expression, we get the value of the limit, 2 3 + 5
@Pi Han Goh Sir, is this better??
Problem Loading...
Note Loading...
Set Loading...
Similar solution with @Aaghaz Mahajan 's
Consider the inequality
( n − 1 m ) ( n − 1 ) ! ( m − n + 1 ) ! m ! ( m − n ) ( m − n + 1 ) m m n m 3 − ( 3 n − 1 ) m + ( n 2 − n ) ⟹ m M ( n ) ⟹ n → ∞ lim n M ( n ) > ( n m − 1 ) > n ! ( m − n − 1 ) ! ( m − 1 ) ! > n 1 > m 2 − 2 n m + n 2 + m − n < 0 < 2 3 n − 1 + ( 3 n − 1 ) 2 − 4 ( n 2 − n ) < 2 3 n − 1 + 5 n 2 − 2 n + 1 = n → ∞ lim 2 n 3 n − 1 + 5 n 2 − 2 n + 1 = 2 3 + 5 Rearranging
Therefore a + b + c = 3 + 5 + 2 = 1 0 .